N-terminal degradation activates the NLRP1B inflammasome - Chui, Ashley J. (Science, 2019)
Intracellular pathogens and danger signals trigger the formation of inflammasomes, which activate inflammatory caspases and induce pyroptosis. The anthrax lethal factor metalloprotease and small-molecule DPP8/9 inhibitors both activate the NLRP1B inflammasome, but the molecular mechanism of NLRP1B activation is unknown. In this study, we used genome-wide CRISPR-Cas9 knockout screens to identify genes required for NLRP1B-mediated pyroptosis. We discovered that lethal factor induces cell death via the N-end rule proteasomal degradation pathway. Lethal factor directly cleaves NLRP1B, inducing the N-end rule–mediated degradation of the NLRP1B N terminus and freeing the NLRP1B C terminus to activate caspase-1. DPP8/9 inhibitors also induce proteasomal degradation of the NLRP1B N terminus but not via the N-end rule pathway. Thus, N-terminal degradation is the common activation mechanism of this innate immune sensor.